Analysis of the Lankford Coefficient Evolution at Different Strain Rates for AA6016-T4, DP800 and DC06 - Lenzen, Matthias; Merklein, Marion (AIP Conference Proceedings 1896(2017)160001, 2017)
None
LFT Import::2019-08-05 (2248)